(x – 2)(x + 2) = 2x – 9:

ajuda


Resposta :

Resposta:

(x - 2) . (x + 2) = 2x - 9

x² + 2x - 2x - 4 = 2x - 9

x² + 2x - 2x - 2x - 4 + 9

x² - 2x + 5 = 0

∆ = b² - 4 . a . c

∆ = (-2)² - 4 . 1 . 5

∆ = 4 - 20

∆ = - 16

delta negativo, não há raízes reais.

Resposta:

[tex]x^{2}[/tex]-4=2x-9

[tex]x^{2}[/tex]-4-2x+9=0

[tex]x^{2}[/tex]+5-2x=0

[tex]x^{2}[/tex]-2x+5=0

x=[tex]\frac{-(-2)+/-\sqrt{-2^{2}-4*1*5 } }{2*1}[/tex]

x=[tex]\frac{2+/-\sqrt{4-20} }{2}[/tex]

x=[tex]\frac{2+/-\sqrt{-16} }{2}[/tex]

x∉R